2021
DOI: 10.1111/jgs.17573
|View full text |Cite
|
Sign up to set email alerts
|

Trends in binge drinking prevalence among older U.S. men and women, 2015 to 2019

Abstract: Background: Recent literature suggests that the gap in prevalence of binge drinking between men and women is closing, but little is known about sex-specific differences in trends and correlates of binge drinking among older Americans.Methods: A total of 18,794 adults, aged 65 years and older were surveyed in the 2015-2019 National Survey on Drug Use and Health. We estimated trends in prevalence of past-month binge drinking (≥5 drinks on the same occasion for men and ≥4 drinks for women), stratified by sex. Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The overall number of older adults reporting binge and heavy drinking was likely grossly underestimated when considering that the binge threshold for older adults is typically considered to be 3 drinks per day for men and 2 drinks per day for women. A study utilizing data from the 2014–2019 National Health Interview Surveys reported that the estimated prevalence of past-month binge drinking among men 65 years or older significantly increased from 12.8% in 2015 to 15.7% [ 15 ]. The estimated prevalence of lifetime, past year, and past month substance use in adults aged 65 and older is described in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The overall number of older adults reporting binge and heavy drinking was likely grossly underestimated when considering that the binge threshold for older adults is typically considered to be 3 drinks per day for men and 2 drinks per day for women. A study utilizing data from the 2014–2019 National Health Interview Surveys reported that the estimated prevalence of past-month binge drinking among men 65 years or older significantly increased from 12.8% in 2015 to 15.7% [ 15 ]. The estimated prevalence of lifetime, past year, and past month substance use in adults aged 65 and older is described in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Men still generally consume more alcohol than women, but nowadays, the gaps are narrowing [ 32 ]. Previous studies report higher rates of alcohol use in men, including binge drinking [ 33 , 34 ] and alcohol dependence [ 35 ]. Biological factors, such as differences in body composition [ 36 ] and metabolism [ 37 ], may partially explain these discrepancies.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, the proportion of older adults who use cannabis or alcohol has risen sharply ( Grant et al, 2017 ; Han, Moore, Sherman, Keyes, & Palamar, 2017 ; Han, Sherman, et al, 2017 ). Past-year cannabis use among adults aged ≥65 in the United States (US) rose from 0.4% in 2006 to 4.2% in 2018 ( Han, Moore, et al, 2017 ; Han & Palamar, 2020 ), and past-month binge drinking increased from 8.1% in 2005/2006 to 11.1% in 2019 ( Al-Rousan, Moore, Han, & Palamar, 2022 ; Han, Moore, et al, 2017 ). With the increase in both cannabis and alcohol use, associations have been established between cannabis use and binge drinking among older adults ( Al-Rousan, Moore, Han, Ko, & Palamar, 2022 ; Han, Moore, et al, 2017 ; Han, Moore, Ferris, & Palamar, 2019 ; Han, Sherman, et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Past-year cannabis use among adults aged ≥65 in the United States (US) rose from 0.4% in 2006 to 4.2% in 2018 ( Han, Moore, et al, 2017 ; Han & Palamar, 2020 ), and past-month binge drinking increased from 8.1% in 2005/2006 to 11.1% in 2019 ( Al-Rousan, Moore, Han, & Palamar, 2022 ; Han, Moore, et al, 2017 ). With the increase in both cannabis and alcohol use, associations have been established between cannabis use and binge drinking among older adults ( Al-Rousan, Moore, Han, Ko, & Palamar, 2022 ; Han, Moore, et al, 2017 ; Han, Moore, Ferris, & Palamar, 2019 ; Han, Sherman, et al, 2017 ). However, a more comprehensive examination of the current use of both substances by older adults is needed.…”
Section: Introductionmentioning
confidence: 99%